Time-resolved effect of interferon-alpha 2a on activities of nuclear factor kappa B, pregnane X receptor and on drug disposition genes - Theile, Dirk; Wagner, Lelia; Bay, Cindy; Haefeli, Walter E.; Weiß, Johanna (Pharmaceutics, 2021)
Interferon-alpha (IFN-α) is suggested to cause pharmacokinetic drug interactions by lowering expression of drug disposition genes through affecting the activities of nuclear factor kappa B (NF-ĸB) and pregnane X receptor (PXR). The time-resolved impact of IFN-α 2a (1000 U/mL; 5000 U/mL; 2 h to 30 h) on the activities of NF-ĸB and PXR and mRNA expression (5000 U/mL; 24 h, 48 h) of selected drug disposition genes and on cytochrome P450 (CYP3A4) activity in LS180 cells (5000 U/mL; 24 h, 48 h) was evaluated using luciferase-based reporter gene assays, reverse transcription polymerase chain reaction, and luminescence-based CYP3A4 activity assays. The cross-talk between NF-ĸB activation and PXR suppression was evaluated by NF-ĸB blockage (10 µM parthenolide). IFN-α 2a initially (2 h, 6 h) enhanced NF-ĸB activity 2-fold and suppressed PXR activity by 30%. mRNA of CYP3A4 was halved, whereas UGT1A1 was increased (1.35-fold) after 24 h. After 48 h, ABCB1 expression was increased (1.76-fold). CYP3A4 activity remained unchanged after 24 h, but was enhanced after 48 h (1.35-fold). IFN-α 2a demonstrated short-term suppressive effects on PXR activity and CYP3A4 mRNA expression, likely mediated by activated NF-ĸB. Longer exposure enhanced CYP3A4 activity. Clinical trials should evaluate the relevance by investigating the temporal effects of IFN-α on CYP3A4 using a sensitive marker substrate.
Gesehen am 14.07.2021